Predictors of exercise participation in ambulatory and non-ambulatory older people with multiple sclerosis - Ploughman,Michelle; Harris,Chelsea; Wallack,Elizabeth M.; Drodge,Olivia; Beaulieu,Serge; Mayo,Nancy; Health Lifestyle and Aging with MS Canadian Consortium (PeerJ, 2015)
Background. Exercise at moderate intensity may confer neuroprotective benefits in multiple sclerosis (MS), however it has been reported that people with MS (PwMS) exercise less than national guideline recommendations. We aimed to determine predictors of moderate to vigorous exercise among a sample of older Canadians with MS who were divided into ambulatory (less disabled) and non-ambulatory (more disabled) groups. Methods. We analysed data collected as part of a national survey of health, lifestyle and aging with MS. Participants (n = 743) were Canadians over 55 years of age with MS for 20 or more years. We identified ‘a priori’ variables (demographic, personal, socioeconomic, physical health, exercise history and health care support) that may predict exercise at moderate to vigorous intensity (>6.75 metabolic equivalent hours/week). Predictive variables were entered into stepwise logistic regression until best fit was achieved. Results. There was no difference in explanatory models between ambulatory and non-ambulatory groups. The model predicting exercise included the ability to walk independently (OR 1.90, 95% CI [1.24–2.91]); low disability (OR 1.50, 95% CI [1.34–1.68] for each 10 point difference in Barthel Index score), perseverance (OR 1.17, 95% CI [1.08–1.26] for each additional point on the scale of 0–14), less fatigue (OR 2.01, 95% CI [1.32–3.07] for those in the lowest quartile), fewer years since MS diagnosis (OR 1.58, 95% CI [1.11–2.23] below the median of 23 years) and fewer cardiovascular comorbidities (OR 1.55 95% CI [1.02–2.35] one or no comorbidities). It was also notable that the factors, age, gender, social support, health care support and financial status were not predictive of exercise. Conclusions. This is the first examination of exercise and exercise predictors among older, more disabled PwMS. Disability is a major predictor of exercise participation (at moderate to vigorous levels) in both ambulatory and non-ambulatory groups suggesting that more exercise options must be developed for people with greater disability. Perseverance, fatigue, and cardiovascular comorbidities are predictors that are modifiable and potential targets for exercise adherence interventions.
Keywords: Disability; Physical activity; Rehabilitation; Exercise behavior; Physiotherapy; Progressive multiple sclerosis; Perseverence; Resilience; Self-efficacy; Depression